2023
DOI: 10.1097/01.hjh.0000912884.68946.a2
|View full text |Cite
|
Sign up to set email alerts
|

S-04-6: Cardiovascular End Points and Mortality Are Not Closer Associated With Central Than Peripheral Pulsatile Blood Pressure Components

Abstract: Pulsatile blood pressure (BP) confers cardiovascular risk. Whether associations of cardiovascular endpoints are tighter for central than peripheral systolic or pulse pressure (cSBP, pSBP, cPP, pPP) is uncertain. Among 5608 participants (54.1% women; mean age, 54.2 years) enrolled in nine studies, median follow-up was 4.1 years. cSBP and cPP, estimated tonometrically from the radial waveform, averaged 123.7 and 42.5 mm Hg, and pSBP and pPP 134.1 and 53.9 mm Hg. The primary composite cardiovascular endpoint occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The adjusted standardized hazard ratios of the primary cardiovascular endpoint were 1.50 (95% CI, 1.33–1.70) for central systolic BP, 1.49 (95% CI, 1.33–1.67) for peripheral systolic BP, 1.36 (95% CI, 1.19–1.54) for central pulse pressure, and 1.34 (95% CI, 1.19–1.51) for brachial pulse pressure. Adding central BPs to a model with brachial BPs did not increase the model fit (generalized R 2 increments ≤.003%) 8 . Once again, it showed that, at least in adult populations, central and brachial BPs were associated with cardiovascular complications at a similar strength.…”
Section: Central Versus Brachial Bp As a Risk Factormentioning
confidence: 77%
See 4 more Smart Citations
“…The adjusted standardized hazard ratios of the primary cardiovascular endpoint were 1.50 (95% CI, 1.33–1.70) for central systolic BP, 1.49 (95% CI, 1.33–1.67) for peripheral systolic BP, 1.36 (95% CI, 1.19–1.54) for central pulse pressure, and 1.34 (95% CI, 1.19–1.51) for brachial pulse pressure. Adding central BPs to a model with brachial BPs did not increase the model fit (generalized R 2 increments ≤.003%) 8 . Once again, it showed that, at least in adult populations, central and brachial BPs were associated with cardiovascular complications at a similar strength.…”
Section: Central Versus Brachial Bp As a Risk Factormentioning
confidence: 77%
“…The anatomic proximity of the aorta to heart, brain, and kidney gives rise to the hypothesis that central BP might be a better reflection of pulsatile pressure load of the target organs and a better predictor of outcomes than peripheral BP. However, up to now the evidence supporting the hypothesis remains inconsistent 7,8 …”
Section: Ntroductionmentioning
confidence: 99%
See 3 more Smart Citations